Measuring the Efficiency of the State Administration Through the Key Performance Indicators - Hak, Mario; Devčić, Anton (European Scientific Journal, ESJ, 2017)
Efficiency has long played a central role in the contested terrain of public administration values. The theoretical part of this paper explains the role and importance of organizational theory at the micro and macro level. The new public management movement was only the latest demand that public organizations promote efficiency by adopting business methods. This paper analyzes the existing business processes and explores how to determine the optimal model of business processes in the Tax Administration. The goal of this model of business is to increase business efficiency and reflecting on all users of the Tax Administration.